Exploring socio-economic impact assessment indicators for musical events in Sarawak: a local stakeholders' based approach - Affandy, Rahmatullah (2025)
Acclaimed as the "Musical State" by National Geographic, Sarawak has firmly established itself as a prominent hub for music tourism through the successful organisation of various high-profile musical events. Flagship festivals such as the Rainforest World Music Festival (RWMF), the Borneo Jazz Festival and the Sarawak International Festival of Music and Arts (SIFMA), organised by the Sarawak Tourism Board (STB), have positioned Sarawak as a leader in music tourism on both national and international platforms. This research investigates the socio-economic impacts of these musical events on local stakeholders and develops indicators to measure these impacts. A qualitative research methodology was adopted, involving semi-structured interviews with 12 purposively selected stakeholders from government agencies, event organisers and local community representatives in Kuching and Miri. The findings demonstrate that while musical events contribute significantly to local economie development, cultural preservation, and community engagement, they also present challenges related to environmental sustainability and equitable benefit distribution. The study introduces the Musical Event Impact Assessment Indicator, a tooi designed to evaluate the extent to which musical events contribute to Sarawak's socio-economic development in a manner that is economically, environmentally and socially sustainable. These findings offer valuable insights for policymakers in formulating strategies and regulations to further enhance the music tourism sector. Moreover, the study provides event organisers with practical recommendations to optimise the planning and execution of musical events, ensuring sustained benefits for all stakeholders.